Antituberculosis: Synthesis and Antimycobacterial Activity of Novel Benzimidazole Derivatives. (4th December 2013) - Keng Yoon, Yeong; Ashraf Ali, Mohamed; Choon, Tan Soo; Ismail, Rusli; Chee Wei, Ang; Suresh Kumar, Raju; Osman, Hasnah; Beevi, Farzana
Abstract : A total of seven novel benzimidazoles were synthesized by a 4-step reaction starting from 4-fluoro-3-nitrobenzoic acid under relatively mild reaction conditions. The synthesized compounds were screened for their antimycobacterial activity against M. tuberculosis H37 Rv (MTB-H37 Rv) and INH-resistant M. tuberculosis (INHR-MTB) strains using agar dilution method. Three of them displayed good activity with MIC of less than 0.2  μ M. Compound ethyl 1-(2-(4-(4-(ethoxycarbonyl)-2-aminophenyl)piperazin-1-yl)ethyl)-2-(4-(5-(4-fluorophenyl)pyridin-3-ylphenyl-1H-benzo[d]imidazole-5-carboxylate (5g ) was found to be the most active with MIC of 0.112  μ M against MTB-H37 Rv and 6.12  μ M against INHR-MTB, respectively.